EFFECT OF CAPITAL MANAGEMENT TO COMPANIES PERFORMANCE IN PAKISTAN TEXTILE SECTOR (World Bulletin of Management and Law, 2024)
The ongoing research examines how managing working capital influences a company's performance, considering the moderating impact of ownership structure. A sample of 77 companies over the period 2011-2015 was analyzed. Through a fixed-effect model, the study revealed a significant negative correlation between leverage, average collection period, and quick ratio with firm performance, whereas current ratio, account payable, and inventory turnover showed a positive impact on firm performance. Moreover, the study found that institutional ownership positively influences the relationship between working capital and firm performance, while managerial ownership has a negative influence. Hence, it is recommended that owners and managers handle their resources effectively to enhance profitability. Additionally, investors and shareholders should take into account the levels of institutional and managerial ownership when making investment decisions.